(untitled) (Biodiversitas Journal of Biological Diversity, 2008)
The incident of hyperhydricity was a common problem in propagated carnation (Dianthus caryophyllus L.) during in vitro culture. Due to its possible relations with the decrease in phenotypic performance of plantlets, the observation on the occurrence of hyperhydricity was conducted on several in vitro conserved carnation cultivars. The research was conducted from July 2007 to August 2008 at The Indonesian Ornamental Crops Research Institute, Cianjur, West Java. A complete factorial experiment with 24 replications was designed to accomplish the combination of two factors. The first factor was six commercial carnation cultivars, namely light pink candy, malaga, opera, white candy, liberty and pink maladi, while the seconds dealt with type of conservation media, i.e. ½MS+DMSO 3%, ½MS+DMSO 3%+3% sucrose and control (½MS+3% sucrose). The results showed that the percentage of hyperhydric plantlet and plantlet viability after in vitro conservation were varied among carnation cultivars. Single treatment of sucrose had the least capacity in inducing plantlet resistance to low temperature conditions during in vitro conservation. Supplemental DMSO postponed the occurrence of hyperhydricity and with the existence of sucrose, higher plantlet viability were achieved. Key words: carnation (Dianthus caryophyllus L.), cultivar, hyperhydricity, plantlet viability, in vitro conservation.